Using a rotating training simulator to train rotational movements in aikido techniques - Mroczkowski, A. (Journal of Combat Sports and Martial Arts, 2013)
Background. The aim of the study is to present the opportunities of using a rotating training simulator to practice aikido techniques involving rotational movements. Material and methods. 49 male students aged 21-23 years participated in the experiment. The subjects were divided into two groups. The experimental group A comprised 24 subjects while the comparative group B comprised 25 subjects. The students were taught ryokatadori kokyo nage technique. The experimental group additionally used rotating training equipment. Correct performance of a technique was scored using 1-10 point scale. The assessment was based on film analysis. Among the students from the experimental group a survey was carried out to study their opinions on using a rotating training simulator in learning aikido techniques involving rotational movements. Results. Group A obtained a significantly higher mean score for aikido technique performance compared with Group B. It was found that the results obtained from both groups significantly differed for p<0.05. The survey results indicate that the subjects using the training simulator confirmed the efficiency of this device to learn aikido techniques involving rotational movements. Conclusions. Using the training simulator enabled quicker acquisition of aikido techniques. The presented rule of the rotating training simulator and the survey results indicate that this device can be used in teaching/learning aikido techniques involving rotational movements. Using the training simulator resulted in a more effective shortening of the circle radius where the practitioners moved, thus increasing the value of the centrifugal force acting on the attacker. It is also possible to eliminate such errors as excessive head and trunk horizontal tilt while performing ryokatadori kokyo nage technique in randori style.